ANALISIS PERAN GURU DALAM PENCEGAHAN DAN PENANGANAN BULLYING DI SEKOLAH DASAR - Mukhlifatul Matukoh; Darnolis; Afwa Lailatun Nisa; Oman Farhurohman (STKIP Subang, 2026)
This research is motivated by the increasing number of cases of violence and bullying in education, particularly in elementary schools. Data from the Indonesian Child Protection Commission (KPAI) and the Indonesian Child Protection Commission (JPPI) show an increase in cases from 285 in 2023 to 573 in 2024, with 31% of these cases related to bullying. This condition is concerning because the impacts of bullying are very broad, ranging from declining academic achievement, social alienation, to psychological disorders such as depression and trauma, for both victims and perpetrators. Therefore, this study aims to examine the role of teachers in preventing and handling bullying and analyze strategies used to create a safe and comfortable school environment. The method used is a literature review by analyzing various academic sources such as relevant articles and journals. Data collection was carried out through documentation and searching for reliable sources to ensure the accuracy of the information. The results show that teachers have a very important role in overcoming bullying through seven main functions: preventing, handling, providing advice, motivating, guiding, directing, and evaluating. Prevention efforts are carried out by instilling the values ​​of empathy and tolerance in learning. Meanwhile, in case management, teachers play a role in identifying problems, mediating conflicts, and providing support to both victims and perpetrators. Furthermore, collaboration between teachers, parents, and the school is crucial in building a school culture that rejects all forms of bullying for the well-being of students.